HOLISTIC MANAGEMENT WITH FAMILY DOCTOR APPROACH TO A 31-YEAR-OLD MALE PATIENTS WITH TUBERCULOSIS - Arif, Athiyah Ulya; Tasmin, H; Fitriani, Rini (Al-Iqra Medical Journal : Jurnal Berkala Ilmiah Kedokteran, 2022)
Â This study aimed to identify risk factors, causes, clinical manifestations and management using a holistic family medicine approach to patients in accordance with evidence-based medicine. This study is a case report. Primary data was obtained from history taking (directly from the patient and indirectly from the patient's family), physical examination, patient home visits, psychosocial and environmental conditions. Secondary data obtained from medical records of the patient at the health center. The assessment was based on the holistic diagnosis. The results A 31-year old male was diagnosed with tuberculosis. The risk factors that affect are the patient often gathers with his friends with the same complaint, smokes and drinks alcohol. The results of the evaluation showed that the patient's complaints had decreased, the patient's knowledge about tuberculosis was also increased and the patient's behavior related to risk factors was also reduced. The limitations of this study is home visit only a few times due to limited time and the pandemic.